2021
DOI: 10.1007/s10570-021-03971-y
|View full text |Cite
|
Sign up to set email alerts
|

Ag@ZIF-67 decorated cotton fabric as flexible, stable and sensitive SERS substrate for label-free detection of phenol-soluble modulin

Abstract: Although strategies of compositing noble materials and Zeolitic imidazolate frameworks (ZIFs) have been used to enhance the performance of ZIF-based surface-enhanced Raman scattering (SERS) substrates, the enhancement process still remains unclear and the sampling process with powder-form substrates is challenging for practical applications. In this study, a exible SERS substrate with silver (Ag) nanoparticle decorated ZIF-67 as the active materials and cotton fabric as the supporting framework is developed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In Figure 3A, the peaks seen around 474, 544, 591, 707, 751, 761, 980, 1051, 1152, 1212, 1234, and 1308 cm −1 are the characteristic Raman peaks of g‐C 3 N 4 proclaims the successful exfoliation of g‐C 3 N 4 43–45 . In Figure 3B (red line), the characteristic Raman peaks of ZIF‐67 can be seen obviously 46,47 . It can be syllogized from Figure 3B (blue line) that the peaks belonging to ZIF‐67 are dominant owing to the composition.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In Figure 3A, the peaks seen around 474, 544, 591, 707, 751, 761, 980, 1051, 1152, 1212, 1234, and 1308 cm −1 are the characteristic Raman peaks of g‐C 3 N 4 proclaims the successful exfoliation of g‐C 3 N 4 43–45 . In Figure 3B (red line), the characteristic Raman peaks of ZIF‐67 can be seen obviously 46,47 . It can be syllogized from Figure 3B (blue line) that the peaks belonging to ZIF‐67 are dominant owing to the composition.…”
Section: Resultsmentioning
confidence: 87%
“…[43][44][45] In Figure 3B (red line), the characteristic Raman peaks of ZIF-67 can be seen obviously. 46,47 It can be syllogized from Figure 3B (blue line) that the peaks belonging to ZIF-67 are dominant owing to the composition.…”
Section: Structural and Morphological Studiesmentioning
confidence: 96%
“…23 Addition of small amounts of MOFs into the polymer matrix reduces the conductivity loss and improves the U e and η values of polymer dielectrics at high temperatures. 24 Dimethylimidazolium cobalt (ZIF-67), a type of MOF, exhibits excellent thermal and chemical stability 25 and a narrow bandgap (E g = 1.6 eV) 26 similar to that of semiconductors. The narrow E g endows ZIF-67 with exceptional electron affinity (χ F = 5.12 eV) 26 (the detailed analysis is provided in Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…24 Dimethylimidazolium cobalt (ZIF-67), a type of MOF, exhibits excellent thermal and chemical stability 25 and a narrow bandgap (E g = 1.6 eV) 26 similar to that of semiconductors. The narrow E g endows ZIF-67 with exceptional electron affinity (χ F = 5.12 eV) 26 (the detailed analysis is provided in Figure S1). Furthermore, the organic ligands of 2-methylimidazole (2-MiM) in ZIF-67 degrade at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Specific studies on the development of several novel nanomaterials have been reported to assist effective Raman platforms including nanogold film-based Raman detection of rhodamine 6G and p-nitrophenol [28], Raman detection of multiple analytes based on Ag nanoparticle-modified SiO 2 nanofibrous [29], Ag nanostructure-assisted Raman sensing for monofluoroacetic acid [30], Ag nanoparticle-introduced Raman detection of carbofuran [31], on-site Raman detection of 1,2,3-benzotriazole on colloidal lignin particles [32], Ag-capped silicon nanopillar-based Raman detection of ochratoxin A [33], nano-shell composite array-based Raman sensor for antioxidant [34], and bimetallic plasmonic nanoparticle-assisted Raman detection of hazardous contamination [35]. Moreover, a series of scientific reports on several special metal-organic framework (MOF) structures has been investigated, leading to successful fabrication of novel Raman substrates applied in trace detection of phenol red [36], phenol-soluble modulin [37], and engine oil [38].…”
Section: Introductionmentioning
confidence: 99%